PENILAIAN ORGANOLEPTIK FERMENTASI PAKAN KOMPLIT TERNAK KAMBING BERBASIS PUTAK DAN TEPUNG IKAN - bambang hadi sutanto (Partner, 2019)
This study aims to utilize the availability of local food such as gamal leaves, corn klobot, putak, rice bran and fish meal through a touch of fermentation technology. The design used in this study was a completely randomized design with 4 treatments and 5 replications. This study assessed organoleptic fermentation of complete feed with 0, 3, 6 and 9 weeks fermentation time in anaerobic conditions with organoleptic research variables (color, aroma, texture) Organoleptic results showed that the fermentation period of 3 weeks and 6 weeks (33.3%) showed the brightest color of complete fermented feed, 9 weeks fermentation time showed the most preferred aroma level (55.5%), 6 weeks fermentation time showed texture the softest (55.5%). The conclusion of acceptance of complete feed fermentation time to color, aroma and texture was fermentation time for 6 weeks (44.4%).